Dyslexia a very short introduction - Snowling, Margaret 1955- (Very short introductions, 2019)
Dyslexia is gaining increasing recognition as a relatively common learning disorder. Margaret Snowling introduces the exciting research surrounding dyslexia, considering potential causes, the neuroscience behind it and attempts to understand how it works, and the various strategies and interventions which can help people with dyslexia today